Validation of the Vocational Identity Status Assessment (VISA) Using Chinese Technical College Students. (November 2019) - Zhang, Jiahong; Chen, Gaowei; Yuen, Mantak
Developing a vocational identity is one of the most important tasks facing any adolescent, and vocational identity has become a focus of attention in career education and guidance for decades. However, few studies have been conducted on this topic in China due to a lack of relevant measures. The purpose of this study was to validate a Chinese version of the Vocational Identity Status Assessment (VISA) using 1, 650 Chinese technical college students. The 30-item VISA–Chinese Version was found to have sound reliability and validity and with measurement invariance across age groups. This study contributes to the vocational identity literature by demonstrating the usefulness of VISA–Chinese Version.